THE STEP-BY-STEP METHODOLOGY OF FORMING COMPETENT PERSONNEL - Normatova Muqaddas Baxodirovna; Normatova Muqaddas Baxodirovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the theoretical and practical foundations of forming competent personnel in the context of globalization, digital transformation, and educational modernization. It presents a step-by-step methodology that integrates needs  analysis,  competence-based  education,  innovative  teaching  technologies, and lifelong professional development. The paper also discusses socio-psychological and motivational factors influencing competence formation. The research concludes that a scientifically  grounded  and  continuously  improved  methodology  for  forming competent  personnel  contributes  to  national  competitiveness,  sustainable  economic growth, and human capital development.